Literature review of studies on the effects of Short tennis on fundamental movement skills of Primary school students - Huang Jie; Md Safwan Samsir; Hasnol Noordin (Human Resource Management Academic Research Society (HRMARS), 2024)
Against the background of the current gradual emphasis on physical education, short tennis has been promoted in Chinese primary school physical education programmes because of its child-friendly characteristics. The adaptability of venues and equipment of short tennis makes it ideal for primary school students, which can not only improve their fundamental movement skills, but also increase the fun and participation of physical activities. Through an extensive review and analysis of national and international literature, this paper examines the practical effects of short tennis in enhancing the fundamental movement skills of primary school students. It is found that this physical activity not only improves students' motor skills, but also helps to enhance their social skills and mental health. China's education policy also provides strong support for the promotion of short tennis, using physical activity as a means to enhance students' overall fitness and motor skills. Through a comprehensive literature review and analysis, this paper highlights the potential and educational value of short tennis in promoting the development of fundamental movement skills among primary school students, providing new perspectives and practical guidance for future educational practice and academic research.